A comparison of the marginal fit and mechanical properties of a zirconia dental crown using CAM and 3DSP. Issue 7 (12th August 2019) - Hsu, Huang-Jan; Lee, Shyh-Yuan; Jiang, Cho-Pei; Lin, Richard
Abstract : Purpose: This study aims to compare the marginal fit, flexural strength and hardness for a ceramic premolar that is constructed using dental computer aided machining (CAM) and three-dimensional slurry printing (3DSP). Design/methodology/approach: Dental CAM and 3DSP are used to fabricate a premolar model. To reduce the fabrication time for 3DSP, a new composition of solvent-free slurry is proposed. Before it is fabricated, the dimensions of the green body for the premolar model are enlarged to account for the shrinkage ratio. A two-stage sintering process ensures accurate final dimensions for the premolar model. The surface morphology of the green body and the sintered premolars that are produced using the two methods is then determined using scanning electronic microscopy. The sintered premolars are seated on a stone model to determine the marginal gap using an optical microscope. The hardness and the flexural strength are also measured for the purpose of comparison. Findings: The developed solvent-free slurry for 3DSP can be used to produce a premolar green body without micro-cracks or delamination. The maximal marginal gap for the sintered premolar parts that are constructed using the green bodies from dental CAM is 98.9 µm and that from 3DSP is 72 µm. Both methods produce a highly dense zirconia premolar using the same sintering conditions. The hardness value for the dental CAM group is 1238.8 HV, which is slightly higher than that for the 3DSP group (1189.4 HV) because there is a difference in the pre-processing of the initial ceramic materials. However, the flexural strength for 3DSP is 716.76 MPa, which is less than the requirement for clinical use. Originality/value: This study verifies that 3DSP can be used to fabricate a zirconia dental restoration device that is as good as the one that is produced using the dental CAM system and which has a marginal gap that is smaller than the threshold value. The resulting premolar restoration devices that are produced by sintering the green bodies that are produced using 3DSP and dental CAM under the same conditions have a similar hardness value, which is four times greater than that of enamel. The flexural strength of 3DSP does not meet the requirement for clinical use.